2007
DOI: 10.1021/jp074737n
|View full text |Cite
|
Sign up to set email alerts
|

Structural Correlations in Liquid Water:  A New Interpretation of IR Spectroscopy

Abstract: We present a new and alternative interpretation of the structure of the IR vibrational mode (nu(OH) band) of pure water. The re-interpretation is based on the influence of the cooperative hydrogen bonding arising from a network of hydrogen bonds in the liquid. The nu(OH) band has six components that are dominated by differences in their O-H bond lengths but deviate from thermodynamically average values due to interactions with the hydrogen bond network. The physical origin of the structure in the nu(OH) band i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 53 publications
11
106
0
Order By: Relevance
“…8 has been decomposed into the four contributions labelled as I i (i = 1, 4) corresponding to the different populations of OH oscillators present in the system. [50][51][52] As shown in previous studies, [36][37][38]40 the sums of the percentage intensities of the two sub-bands found, respectively, at the lowest and highest wavenumbers, i.e. (I 1 + I 2 ) and (I 3 + I 4 ) in Fig.…”
Section: Restructuring Of the Hb Network Of Confined Watersupporting
confidence: 79%
“…8 has been decomposed into the four contributions labelled as I i (i = 1, 4) corresponding to the different populations of OH oscillators present in the system. [50][51][52] As shown in previous studies, [36][37][38]40 the sums of the percentage intensities of the two sub-bands found, respectively, at the lowest and highest wavenumbers, i.e. (I 1 + I 2 ) and (I 3 + I 4 ) in Fig.…”
Section: Restructuring Of the Hb Network Of Confined Watersupporting
confidence: 79%
“…For water, four-body and higher order interactions seem to be negligible with respect to the three-body term (28,29). Hence, the fourth component to the interaction potential is the many-body effect due to H-bonds (30)(31)(32), that minimizes the energy when the H-bonds of nearby molecules assume a tetrahedral orientation. This is accomplished by further adding to the Hamiltonian in Eqs.…”
Section: Cooperative Cell Model Of Watermentioning
confidence: 99%
“…Care must be taken when using deconvolution algorithms and the resulting interpretation, and we previously discussed our deconvolution method in detail. [21] Indeed, we examined the deconvolution as a function of peak shape and the number of components in the n(OH) band and found that the best fit, which minimized both c 2 and the sum of the fit residual, corresponds to six Gaussian peaks. Fitting with Lorentzian line shapes was also explored, but all such fits produced larger errors for both c 2 and the sum of the fit residual and could not reproduce the overall envelope of the n(OH) curve.…”
Section: Deconvolutionmentioning
confidence: 99%
“…[2,3,[14][15][16] Although the OH stretching band [n(OH) band] originates from OÀH vibrations, it is also correlated to the overall structure of water, [6,17,18] because the surrounding H-bonds alter the intermolecular bond and thus change the dipole moment and vibrational spectra. [1,[18][19][20][21] The structure of the n(OH) band can therefore provide information on how the H-bond network is modified by defects. Here we investigate how low-concentration ionic defects modify the H-bond network topology by examining changes in the n(OH) band.…”
Section: Introductionmentioning
confidence: 99%